PENGARUH BELANJA PENDIDIKAN, JUMLAH GURU, DAN TINGKAT KEMISKINAN TERHADAP ANGKA PARTISIPASI SEKOLAH - Fatah, Khoirul; Tridevayanti, Anggita; Imtikhanah, Sobrotul (Neraca, 2023)
This study looked at how much is spent on education, how many teachers there are, and how much poverty there is. 35 districts in the province of Central Java served as the study's sample. Multiple linear regression analysis was the quantitative method used in this study. Secondary data that was used in documentation methods. Education spending had no discernible impact, according to the partial results analysis. There was no discernible impact of the number of teachers. School enrollment rates were significantly impacted by poverty levels. The variables relating to education spending, the number of teachers, and the degree of poverty all had a significant impact on the percentage of students who attended school.